2012
DOI: 10.1016/j.bbr.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Increased anxiety-like behaviors in rats experiencing chronic inflammatory pain

Abstract: For many patients, chronic pain is often accompanied, and sometimes amplified, by co-morbidities such as anxiety and depression. Although it represents important challenges, the establishment of appropriate preclinical behavioral models contributes to drug development for treating chronic inflammatory pain and associated psychopathologies. In this study, we investigated whether rats experiencing persistent inflammatory pain induced by intraplantar injection of complete Freund's adjuvant (CFA) developed anxiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
3
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(129 citation statements)
references
References 57 publications
10
111
3
2
Order By: Relevance
“…Similar to these previous studies in mice, our current study further confirmed that CFA-induced inflammatory pain did not alter OF and social interaction behaviors at 10 days after inflammation in both C57BL/6J and FVB/NJNju strains. In contrast, there is a large body of work on rats showing changes in anxiety and depression-like behaviors occurring in neuropathic and inflammatory pain status [25,26,[28][29][30][31]. Notably, in the present study both C57BL/6J and FVB/NJNju mice with CFA-inflammatory pain showed decreased open-arm entry in the EPM test, although there were no differences in the OF test.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Similar to these previous studies in mice, our current study further confirmed that CFA-induced inflammatory pain did not alter OF and social interaction behaviors at 10 days after inflammation in both C57BL/6J and FVB/NJNju strains. In contrast, there is a large body of work on rats showing changes in anxiety and depression-like behaviors occurring in neuropathic and inflammatory pain status [25,26,[28][29][30][31]. Notably, in the present study both C57BL/6J and FVB/NJNju mice with CFA-inflammatory pain showed decreased open-arm entry in the EPM test, although there were no differences in the OF test.…”
Section: Discussioncontrasting
confidence: 78%
“…However, experimental animal studies using persistent pain models found conflicting results as to whether injured mice show changes in anxiety-like behaviors [9,19,[25][26][27][28]. For example, Hasnie et al reported that nerve injury did not alter OF or EPM behavior at 1, 2 or 4 weeks after injury in C57BL/6J mice [26].…”
Section: Discussionmentioning
confidence: 99%
“…Diazepam is a classic anxiolytic, which has been demonstrated in numerous clinical studies [42] and various animal models with pain [40,43]. The present study also observed anxiolytic effect of diazepam in the acid-induced CWP model.…”
Section: Research Fu-zen Shawsupporting
confidence: 78%
“…The test consisted in measuring for 5 min the number and duration of active social interactions (sniffing, grooming, playing or chasing) between a pair of rats of the same sex, from different litters, with both exposed to the same experimental condition [19]. The body weights of each pair did not differ by more than 15 g. Simple passive physical contacts between the animals were not considered as social interactions, as previously described [21]. …”
Section: Methodsmentioning
confidence: 99%